-4b+8+6b+2=b+1+6

Simple and best practice solution for -4b+8+6b+2=b+1+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4b+8+6b+2=b+1+6 equation:



-4b+8+6b+2=b+1+6
We move all terms to the left:
-4b+8+6b+2-(b+1+6)=0
We add all the numbers together, and all the variables
-4b+6b-(b+7)+8+2=0
We add all the numbers together, and all the variables
2b-(b+7)+10=0
We get rid of parentheses
2b-b-7+10=0
We add all the numbers together, and all the variables
b+3=0
We move all terms containing b to the left, all other terms to the right
b=-3

See similar equations:

| 10x+3=2(5x)+3 | | A.10b+8b+9−18b+3=5+6b−2b−12+7 | | 2.2x=-8.8 | | 2x+24=x+19 | | 4x+6=9-4x | | 2x-7=-7+7x | | x+6-2=-15 | | 10-15p=-30+135p | | .42b-8.3+9.14b=-5.91 | | -46+8+6b+2=b+1+6 | | 5=6x-5x-5 | | 6x+0.3=54.3 | | 5d-9=11d+3 | | 8v+3(1/3v-6)=9v+12 | | v+-194=-91 | | 2x-11+9=x+8 | | 10n-5=165 | | 1.5(x-4)=0.5x+6-5 | | 5x+8=9x+12x2 | | 268=53+l | | 8=2/1(2x+4) | | 50-20=6x | | 6x-(2x-3)+x=-12 | | x+6−2=-15 | | 4(2a-8)=0 | | q+-658=-254 | | 12=n+3+6 | | 2(5x−2)-2x-2=34 | | 13=4(p-8)+9 | | 4j-3j=92 | | 3y-2/8=6y-5/17 | | 7n=105n= |

Equations solver categories